Co-infections exacerbate inflammatory responses in COVID-19 patients, promoting coagulopathy and myocardial injury, leading to increased disease severity - Chang, Xiaoxia; Lai, Yanjun; Zhao, Yingying; Zhao, Jing; Zhang, Yunchao; Qian, Xiaotao; Zhang, Guochao (Frontiers in Immunology, 2025)
ObjectivesSevere COVID-19 infection is characterized by excessive inflammatory responses, hypercoagulation, and microvascular dysfunction. However, limited research has investigated the effects of co-infections on these characteristics in COVID-19 patients. This study aims to explore how co-infections influence inflammation, hypercoagulability, and microvascular dysfunction in hospitalized COVID-19 patients, and to assess their impact on disease progression.MethodsThis was a retrospective cohort study involving 630 COVID-19 inpatients who tested positive for SARS-CoV-2 RNA at Xi’an Ninth Hospital. The patients were categorized into two groups: a severe group (n = 176) and a mild group (n = 454). Additionally, they were further subdivided into a co-infected (n = 106) group and a non-co-infected group (n=524) based on the presence or absence of co-infections. Clinical characteristics and laboratory findings were analyzed and compared between the groups.ResultsIn the co-infected group, 60 patients (56.6%) were classified as severe cases, and 15 (14.2%) died. By comparison, in the non-co-infected group, 97 patients (18.5%) were severe cases, with 4 (0.8%) deaths. The severity and mortality rates were significantly higher in co-infected patients compared to those non-co-infections. The severe and co-infected groups exhibited significantly higher levels of inflammatory cells, inflammatory factors, coagulation biomarkers, and myocardial injury markers compared to the mild and non-co-infected groups. Conversely, lymphocyte counts, RBC counts, HGB, HCT, TP, and ALB levels were significantly lower in the severe and co-infected groups than in the mild and non-co-infected groups. Furthermore, a notable positive correlation was observed among inflammatory factors, coagulation function, and myocardial injury biomarkers in COVID-19 patients.ConclusionCo-infections in COVID-19 patients can trigger severe inflammatory responses. This excessive inflammation may lead to coagulation disorders and myocardial injury, all of which are key contributors to disease progression and deterioration. Therefore, implementing infection prevention measures to minimize the spread of co-infections among hospitalized COVID-19 patients is crucial.